Taxonomy and nomenclature of Kalanchoe tomentosa (Crassulaceae subfam. Kalanchooideae), a variable, completely hairy species from Madagascar - Smith, Gideon F. (Phytotaxa, 2023)
The taxonomy and nomenclature of the Malagasy Kalanchoe tomentosa are reviewed and discussed in a historical context. An amplified description and illustrations are provided for the species and the name K. tomentosa is epitypified.